HYAL2 methylation in peripheral blood as a potential marker for the detection of pancreatic cancer: a case control study - Schott, Sarah; Yang, Rongxi; Stöcker, Sarah; Giese, Nathalia; Bugert, Peter; Bergmann, Frank; Strobel, Oliver; Hackert, Thilo; Sohn, Christof; Burwinkel, Barbara (OncoTarget, 2017)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy which is mostly diagnosed in advanced and inoperable stages though surgery remains the only curable therapeutic approach. Early detection markers are urgently needed to improve diagnosis. Altered hyaluronoglucosaminidase 2 gene (HYAL2) DNA methylation in peripheral blood is known to be associated with malignancy at early stage but has not been evaluated in PDAC patients. This study evaluates the association between blood-based HYAL2 methylation and PDAC by a case-control study with 191 controls and 82 PDAC patients. Decreased methylation of all four investigated HYAL2 methylation sites showed highly significant association with PDAC (odds ratio (ORs) per −10% methylation ranging from 2.03 to 12.74, depending on the specific CpG site, p < 0.0001 for all). HYAL2 methylation sites were also distinguishable between stage I&II PDAC (61 subjects) and controls (ORs per-10% methylation from 3.17 - 23.04, p < 0.0001 for all). Thus, HYAL2 methylation level enabled a very good discrimination of PDAC cases from healthy controls (area under curve (AUC) = 0.92, 95% Confidence interval (C.I.): 0.88 - 0.96), and was also powerful for the detection of PDAC at stage I&II (AUC = 0.93, 95% C.I.: 0.89 - 0.98). Moreover, the blood-based HYAL2 methylation pattern was similar among PDAC patients with differential clinical characteristics, and showed no correlation with the overall survival of PDAC patients. Our study reveals a strong association between decreased HYAL2 methylation in peripheral blood and PDAC, and provides a promising blood-based marker for the detection of PDAC.
Gesehen am 20.08.2018